Unveiling inverse piezoelectricity and field induced nonvolatile strain in 2D TMDs - Utpreksh Patbhaje; Rupali Verma; Jeevesh Kumar; A Ansh; Mayank Shrivastava (npj 2D Materials and Applications)
Abstract The advancement of transition metal dichalcogenide (TMD)-based electronics technology demands thorough understanding of dominant electrical instability mechanisms. Through rigorous analysis, we identify a previously unrecognized non-volatile strain in TMDs that emerges during electrical operation, distinct from known instability mechanisms. Strain induced by electrical operation in TMD devices distinctly impacts electron and hole transport, as evidenced by the performance evolution of our ambipolar MoSe2 field effect transistors (FETs). Raman spectroscopy, photoluminescence, and work function measurements reveal tensile strain in the channel and compressive strain near the contacts. This strain mismatch between the channel and contact regions disrupts charge transport and leads to instability in electrical performance. These instabilities are inevitable as they originate from the interaction between the electric field and the piezoelectric properties of TMDs and are expected to intensify in the field-accelerated downscaled devices. If unaddressed, these instabilities could severely limit the practical and commercial viability of TMD-based electronics.